52 Overuse or informed patient choice? A pilot implementation study of a decision aid for women with early-stage breast cancer considering contralateral prophylactic mastectomy (CPM). (4th December 2019) - Jansen, Jesse; Glassey, Rachael; Serafimovska, Anastasia; Butow, Phyllis; ,
Abstract : Objectives: Guidelines internationally recommend against routinely performing a double mastectomy in a patient with breast cancer in a single breast because it provides minimal improvement of life expectancy with potential for harm. Despite these recommendations, rates of contralateral prophylactic mastectomy (CPM) have been increasing. Research shows that fear of cancer recurrence and inaccurate beliefs about survival extension are key drivers, but anxiety associated with repeated screening in the remaining breast and aesthetical reasons (e.g. having a balanced chest) are important other factors. Women differ in the relative importance they place on these factors and therefore calls have now been made to carefully inform women about the potential benefits and harms of CPM through shared decision-making. We aimed to pilot test the implementation of a patient decision aid (PtDA) for women with early-stage breast cancer at average risk of contralateral breast cancer considering CPM. Method: The PtDA was developed according to International Patient Decision Aid Standards and reviewed by an expert advisory group including breast cancer consumer representatives. After confirming acceptability in a qualitative interview study involving 23 women with a history of early-stage breast cancer, we used an implementation theoretical approach to gain understanding of the barriers and facilitators to PtDA adoption. The PtDA was delivered during or after consultations between breast cancer surgeons, and women with early-stage breast cancer with an average risk of contralateral breast cancer who enquired about the option of having CPM. We included women (a) newly diagnosed, or (b) having a follow-up consultation. Data was collected using qualitative interviews with patients and clinicians (latter not reported in this presentation). Interviews were audio-recorded, transcribed verbatim, and analysed thematically using framework analysis. Results: So far, we have recruited 16 breast surgeons in 5 hospitals (public and private) across NSW and WA, Australia and included 18 patients (66% of target sample size of 30). Preliminary analysis suggests that the PtDA was a useful resource that helped participating women to 'stop, pause and think' about all aspects of the decision to have CPM or not. For many women the information about the low mortality benefit of CPM was surprising and reduced their anxiety for cancer recurrence in the other breast. Women valued how the PtDA validated symmetry as a reason for CPM. The PtDA seemed to confirm existing preferences rather than shift treatment intentions. Most women expressed the importance of fully informing all women with early-stage breast cancer about the option of having CPM, although some acknowledged that offering choice might inadvertently promote CPM in women who might otherwise not have considered it. Conclusions: These findings highlight the challenges of supporting patient autonomy in a time of medical overuse, and the importance of supporting women with evidence-based information about the benefits and harms of CPM so that they can make an informed decision. Future studies are needed to evaluate the impact of the CPM PtDA on actual treatment decisions and short- and long-term outcomes in women with early-stage breast cancer.